PROFILING GAYA BELAJAR SISWA KELAS VI SEBAGAI DASAR PEMBELAJARAN BERDIFERENSIASI DI SDN 6 PURWAWINANGUN - Sintia; Reza Adi Pangestu; Reti Ursila; Ilah Nurlaelah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify learning style profiles of sixth-grade students at SDN 6 Purwawinangun as the basis for implementing differentiated learning. The research employed a descriptive qualitative method. Data were collected through observation, interviews, documentation, and a learning style questionnaire based on the Visual, Auditory, and Kinesthetic (VAK) model. Subjects consisted of 23 sixth-grade students. Data analysis followed the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The results revealed that students have varied learning styles: 10 students (43.48%) are Visual-Auditory, 8 students (34.78%) have a combined (Visual-Auditory-Kinesthetic) style, 4 students (17.39%) are Visual-Kinesthetic, and 1 student (4.35%) is Auditory-Kinesthetic. These findings indicate that differentiated learning strategies need to be designed by considering the dominant learning style of each student. Teachers are recommended to apply multimodal instructional strategies that accommodate all three learning style categories to optimize the learning experience and student outcomes in elementary school.